Remnant closure after distal pancreatectomy: current state and future perspectives - Hackert, Thilo; Büchler, Markus W. (The surgeon, 2012)
Remnant closure after distal pancreatectomy remains a surgical challenge and is still associated with a fistula rate of about 30%. Despite numerous technical modifications including the use of stapling devices, artificial patches and glue components, no important progress has been made concerning this topic within the last decade. Although tissue texture, co-morbidities and the type of resection may influence fistula rate, substantial improvement can probably be reached by further technical modifications. In addition to the avoidance of fistula development, the recognition and management of this complication is essential to achieve good postoperative outcome. The present review summarizes the currently available data on technical approaches, incidence and risk factors for failure of remnant closure, fistula-associated complications and management as well as the future perspectives in this field of surgery.